Microteaching Learning Strategies and Their Roles to Improve Teaching Ability of Teacher Students at Islamic Higher Education - Ramang Ramang (Yayasan Keluarga Guru Mandiri, 2023)
Microteaching as a learning medium and teaching practice is very important in meeting the needs of student teaching practice, especially in the Islamic Religious Education study program, Faculty of Tarbiyah and Teacher Training, UIN Datokarama Palu. This study aims to demonstrate microteaching learning strategies and their contribution to the development of quality and teaching skills of teacher students. This research is qualitative descriptive and uses N Vivo Software as a tool or technique for analyzing data. The results of this study concluded that the microteaching learning strategy applied to the Islamic Religious Education study program, UIN Datokarama Palu consisted of two main strategies namely discovery learning and expository method. Discovery learning is a learning strategy that focuses on exploring student interests in carrying out the learning process. The expository method is a learning strategy by providing a general description of aspects of definitions, principles, and concepts about learning materials. The impact of implementing microteaching learning strategies using discovery learning and expository methods is being able to develop student confidence in the teaching process and being able to improve students' abilities in depth about teaching activities.